Analisis Pembentukan Portofolio Saham Optimal menggunakan Pendekatan Model Indeks Tunggal sebagai Dasar Keputusan Investasi - Cindy Devina Setiawan; Vera Intanie Dewi (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
The purpose of this research is identify stocks that are included in the optimal portfolio of 45 stocks that are the most liquid and actively traded on the Indonesia Stock Exchange which are often referred to as LQ45 Index stocks. The research period is December 2017-December 2020. The sampling technique used purposive sampling and 30 companies were selected to be used as research samples. The analytical technique used in this research is using the Single Index This research results showed that there were thirteen stocks of portfolio candidates from thirty stocks researched with the cut-off-rate (C*) of 0,00385. Six of thirteen stocks which have the biggest excess return to beta (ERB) make up the optimum portfolio: ANTM (1.59%), INCO (1.14%), BBCA (1.06%), WIKA (0.67%), PTBA (0.66%), SMGR (0.56%). The optimum portfolio comprises the proportion of funds from the six shares is BBCA (43.40%); ANTM (21.05%); INCO (18.81%), WIKA (6.12%), PTBA (5.85%) and SMGR (4.78%). Expected Return Portfolio and Portfolio Variant are 2.44% and 2.61%, respectively. The conclusion that can be recommended for rational investors is to invest their funds in the optimum portfolio comprises BBCA, ANTM, INCO, WIKA, PTBA and SMGR stocks.